Intestinal Microbial-tissue Complex and Chronic Heart Failure (part 1): Pathogenesis - A. A. Vlasov; S. P. Salikova; N. V. Golovkin; V. B. Grinevich (Рациональная фармакотерапия в кардиологии)
Antigenic and metabolic integration of the intestinal microbiota into the homeostasis of the human body is a factor that claims to play a key role in the pathogenesis of cardiovascular diseases. It acquires special significance against the background of the decrease in blood circulation and congestion in the digestive system during chronic heart failure. Aim of the review is analysis and synthesis of studies results on the role of intestinal microbiocenosis in the pathogenesis of heart remodeling and chronic heart failure. The search for articles was conducted in databases eLIBRARY.RU and Medline for the key terms "gut microbiota (microbiome, microbiocenosis)", "dysbiosis (dysbacteriosis)", "excessive bacterial growth syndrome", "lipopolysaccharide (endotoxin)", "trimethylamine-N-oxide" in combination with the terms "heart failure", "myocardial remodeling", "myocardium" in Russian and English, respectively. We selected articles containing the results of clinical and experimental studies published from 1995 to 2020. Review articles were considered only on the subject of the cited original publications. Most researchers have established the relationship between chronic heart failure and dysfunction and changes in the qualitative and quantitative composition of intestinal microbiocenosis. As negative changes, it is customary to note the proliferation of gram-negative opportunistic bacteria with concomitant endotoxinemia and a decrease in the pool of commensal microbiota. The available data suggest that the participation of the intestinal microbial-tissue complex in the pathogenesis of chronic heart failure and heart remodeling is realized through the activation of a local and then systemic inflammatory response, accompanied by cardiodepressive action of pro-inflammatory cytokines and universal proliferation factors, an imbalance of matrix metalloproteinases and their inhibitors, the initiation of apoptosis, fibrosis, and loss of contractile myocardium. Besides, a decrease in the production of short-chain and polyunsaturated fatty acids and vitamins by the commensal microbiota may be associated with changes in the electrical properties of cardiomyocyte membranes, a decrease in the systolic function of the left ventricle of the heart, and an increase in the risk of sudden cardiac death. It's also shown that the direct cardiotoxic effect of microbial molecules (lipopolysaccharides, peptidoglycans, trimethylamine-N-oxide, etc.), which interact with the receptors of cardiomyocytes and microenvironment cells, can cause the development of myocardial remodeling and its dysfunction. Recent studies have established mechanisms of myocardial remodeling mediated by microbial molecules, which may be associated with new strategies for the treatment and prevention of heart failure.